2016
DOI: 10.9734/bjmmr/2016/29162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Gender Variation in Normal Pituitary Gland Height Using Magnetic Resonance Imaging

Abstract: Aims:The aim of this study was to analyze the age and sex related changes in pituitary gland height in a selected population from Sudan, and also to compare findings with those of other authors.Study Design: This prospective study included 50 participants (25 males and 25 females; ages range between 2-65 years) underwent brain magnetic resonance imaging (MRI) examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Previous studies also showed a similar trend with regards to the morphology of the pituitary gland with the age and sex of the subjects. 1,10,11,12 The mean pituitary gland height and volume in our study was 5.11 ± 1.54mm and 344.49 ± 124.4 m 3 respectively. A study from Nepal by Lamichhane et al reported a mean pituitary height of 5.9 ± 0.3 which was almost similar to our finding (5.1 ± 1.5).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Previous studies also showed a similar trend with regards to the morphology of the pituitary gland with the age and sex of the subjects. 1,10,11,12 The mean pituitary gland height and volume in our study was 5.11 ± 1.54mm and 344.49 ± 124.4 m 3 respectively. A study from Nepal by Lamichhane et al reported a mean pituitary height of 5.9 ± 0.3 which was almost similar to our finding (5.1 ± 1.5).…”
Section: Discussionsupporting
confidence: 43%
“…5 Other studies also found the maximum height of the pituitary gland during the second and/ or third decade of life and gradual decline thereafter. 7,8,10,11,12 Again increase in height was noted at the fifth or/and sixth decade of life. 2,5,7,12 The increase in pituitary height during puberty might be related to the increased production of Follicle-stimulating hormone (FSH) and Luteinizing Hormone (LH) at this time of growth and decrease in the pituitary height in the older age group might be due to changes in the endocrine status with ageing and also physiological atrophy of the pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…The mean pituitary volume for men was 405 ± 118 mm 3 (range 116-896 mm 3 ) and 494 ± 138 mm 3 for women (range 114-1089 mm 3 ), constituting a significant difference (p < 0.001). The mean mid-sagittal pituitary height for men was 4.4 ± 1.4 mm (range 0.7-8.8 mm) and for women 4.9 ± 1.7 mm (range 0.0-11.2 mm), constituting a significant difference (p < 0.001).…”
Section: Resultsmentioning
confidence: 93%
“…The normal development of the pituitary gland is dependent on fluctuating neuroendocrine changes throughout life, thus the pituitary height and volume naturally varies with age and sex across the lifespan [1]. The majority of Magnetic Resonance Imaging (MRI) studies conducted on the normal physiological development of adolescence and adult pituitary size agrees that the pituitary size reaches its peak sometime during the 2nd or 3rd decade of life, and later declines in both men and women [1][2][3][4][5]. There is, however, conflicting results in the literature when it comes to persons above 50 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation